Association Between Frailty and Atrial Fibrillation in Older Adults: The Framingham Heart Study Offspring Cohort - Ariela R. Orkaby; Jelena Kornej; Steven A. Lubitz; David D. McManus; Thomas G. Travison; Jason A. Sherer; Ludovic Trinquart; Joanne M. Murabito; Emelia J. Benjamin; Sarah R. Preis (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2021)
Background Frailty is associated bidirectionally with cardiovascular disease. However, the relations between frailty and atrial fibrillation (AF) have not been fully elucidated. Methods and Results Using the FHS (Framingham Heart Study) Offspring cohort, we sought to examine both the association between frailty (2005–2008) and incident AF through 2016 and the association between prevalent AF and frailty status (2011–2014). Frailty was defined using the Fried phenotype. Models adjusted for age, sex, and smoking. Cox proportional hazards models, adjusted for competing risk of death, assessed the association between prevalent frailty and incident AF. Logistic regression models assessed the association between prevalent AF and new‐onset frailty. For the incident AF analysis, we included 2053 participants (56% women; mean age, 69.7±6.9 years). By Fried criteria, 1018 (50%) were robust, 903 (44%) were prefrail, and 132 (6%) were frail. In total, 306 incident cases of AF occurred during an average 9.2 (SD, 3.1) follow‐up years. After adjustment, there was no statistically significant association between prevalent frailty status and incident AF (prefrail versus robust: hazard ratio [HR], 1.22 [95% CI, 0.95–1.55]; frail versus robust: HR, 0.92 [95% CI, 0.57–1.47]). At follow‐up, there were 111 new cases of frailty. After adjustment, there was no statistically significant association between prevalent AF and new‐onset frailty (odds ratio, 0.48 [95% CI, 0.17–1.36]). Conclusions Although a bidirectional association between frailty and cardiovascular disease has been suggested, we did not find evidence of an association between frailty and AF. Our findings may be limited by sample size and should be further explored in other populations.